The trap of agrarian economy. A retrospective analysis of threats to economic security of Ukraine - Serhii Zakharovych (Економіка, управління та адміністрування)
For Ukraine, as for one of the largest exporters of grain and other agricultural products, the agrarian economy is an important source of budget revenues. However, the agrarian model of economic development, like any other raw material economy, creates relatively easy and simple profits that are usually spent on consumption. Thus, it slows down investments in the formation of high-tech industries. And this creates threats to economic security, as it significantly limits the long-term economic prospects of the state in today’s globalized world. The model of agrarian economy began to form in Ukraine (which was then a part of the Polish-Lithuanian Commonwealth) in the XVI century. Back then, Western Europe received large amounts of gold and silver from colonized Latin America. This led to an increase in the amount of money in circulation, and as a result – to rising prices for most goods, including agricultural products. Large landowners took advantage of this moment and became important suppliers of grain grown on their estates. The grain was transported by rivers to the Vistula River and then to Gdansk, an important port on the Baltic Sea, where it was shipped mainly to the Netherlands (at that time – the center of the Western European economy). The owners of grain received large profits, which they spent mainly on consumption and on the development of their estates. They had no need to improve agricultural production – grain was grown by serfs. Mass production of grain in the farms of landlords kept peasants from migrating to cities, although in other countries they usually sought work in cities, becoming craftsmen and contributing to the emergence of the first industrial enterprises. Thus, the development of production in Ukrainian cities was slowed down, as did the expansion of the cities themselves. And although the first signs of capitalist relations (production for sale, integration into European markets of grain and other agricultural products, the use of hired labor, etc.) were already noticeable in the agrarian Ukrainian economy at the end of the XVI century, such agrarian capitalism created a trap of the agrarian economy, from which proved to be impossible to escape over the next centuries.